The Effect of Product Quality and Brand Image on Purchasing Decisions for Yamaha Mio Motorbikes at PT. Jayamandiri Gemasejati Bogor - Sudarijati; Selsa Oktia Rahmawati; Rachmat Gunawan (International Journal of Educational and Life Sciences, 2024)
This study aims to determine the effect of product quality, and brand image on purchasing decisions on Yamaha Mio motorbikes at PT. Jayamandiri Gemasejati Bogor simultaneously and partially. The subject of this research is the buyer of Yamaha Mio product at the company PT. Jayamandiri Gemasejati Bogor. The sample in this study amounted to 100 respondents conducted by purposive sampling. The data analysis technique in this study used the IBM SPSS 25 software application. Data analysis uses descriptive analysis, verification analysis with a quantitative approach. The data analysis method used in this study is multiple linear regression analysis. The results showed that product quality, brand image, and purchasing decisions with good criteria. Simultaneously and partially product quality and brand image have a positive and significant effect on purchasing decisions on Yamaha Mio products at PT. Jayamandiri Gemasejati Bogor